Fenomena Fear of Missing Out (FOMO) Investor Saham dalam Ekosistem Media Sosial Digital: Pengaruh Financial Influencer dan Algoritma Media Sosial melalui Literasi Keuangan - Mangasi Sinurat (Accounting Progress, 2026)
This study aims to analyze the influence of Financial Influencers and Social Media Algorithms on stock investors’ Fear of Missing Out (FOMO) through Financial Literacy as an intervening variable. The development of digital social media has transformed investor behavior in making investment decisions, particularly due to the influence of financial influencer content and social media algorithm systems that intensively display investment-related information to users. This study employed a quantitative approach using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with SmartPLS 4 software. The research sample consisted of 200 stock investors selected using purposive sampling techniques. Data collection was conducted through questionnaires using a Likert scale. The results showed that Financial Influencers and Social Media Algorithms had a positive and significant effect on Financial Literacy and stock investors’ Fear of Missing Out (FOMO). In addition, Financial Literacy also had a positive and significant effect on Fear of Missing Out (FOMO). The indirect effect testing demonstrated that Financial Literacy significantly mediated the influence of Financial Influencers and Social Media Algorithms on stock investors’ Fear of Missing Out (FOMO). This study proves that the development of the digital social media ecosystem plays an important role in shaping modern stock investor behavior, both from rational and psychological investment perspectives.